2019
DOI: 10.1101/715680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic Profiling of Aortic Stenosis and Hypertrophic Cardiomyopathy Identifies Mechanistic Contrasts in Substrate Utilisation

Abstract: BackgroundAortic stenosis (AS) and hypertrophic cardiomyopathy (HCM) are highly distinct disorders leading to left ventricular hypertrophy (LVH), but whether cardiac metabolism substantially differs between these in humans remains to be elucidated.MethodWe undertook a detailed invasive (aortic root and coronary sinus) metabolic profiling in patients with severe AS and HCM in comparison to non-LVH controls, to investigate cardiac fuel selection and metabolic remodelling. These patients were assessed under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Despite several clinical and experimental studies showing metabolic remodeling and inflexibility in hypertrophic and failing hearts, [46][47][48] there are few comprehensive studies in human cardiomyopathies, especially in HCM. 21,49 Here, we present an in-depth multiomics characterization of human HCM myocardium combined with analysis of mitochondrial structure and function. This integrative omics analysis reveals potential molecular mechanisms underlying HCM pathophysiology, including major metabolic derangements across all main biochemical pathways (summarized in Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Despite several clinical and experimental studies showing metabolic remodeling and inflexibility in hypertrophic and failing hearts, [46][47][48] there are few comprehensive studies in human cardiomyopathies, especially in HCM. 21,49 Here, we present an in-depth multiomics characterization of human HCM myocardium combined with analysis of mitochondrial structure and function. This integrative omics analysis reveals potential molecular mechanisms underlying HCM pathophysiology, including major metabolic derangements across all main biochemical pathways (summarized in Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Voros et al (2018) found increased uptake of ketone bodies and FFAs in both patients with heart failure/reduced ejection fraction and patients with aortic stenosis-induced left ventricular hypertrophy 73 . Pal et al (2019) further compared substrate utilization between patients with aortic stenosis and those with hypertrophic cardiomyopathy 74 and identified differential metabolism of longchain acylcarnitines. As described above, Murashige et al (2020) performed comprehensive mapping of cardiac uptake and release of numerous circulating metabolites in patients with preserved or reduced ejection fraction, which revealed that the failing heart relies on more ketones and lactate, has higher protein breakdown, and surprisingly uses almost no glucose 32 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%